Causes of Pneumonia in Children and Modern Solutions for Prevention - Burkhanovich, Sanakulov Abdulatif (Journal of Science in Medicine and Life, 2024)
Pneumonia in children is an acute or less common chronic infectious and inflammatory disease of the respiratory tract, which occurs with damage to the lung tissue (parenchyma) against the background of bacterial, viral, fungal or parasitic infection. The disorder is accompanied by severe symptoms of cough, shortness of breath and general intoxication. Clinical manifestations appear especially in the first years of life. In older patients, except for severe forms of the disease, the symptoms are not so obvious. Pulmonologists and pediatricians are involved in determining the causes of the pathological process. The treatment of the pathological process is also the competence of these specialists. Depending on the form and severity of the disorder, therapy can be outpatient or inpatient, in a hospital setting.